Contamination of per- and polyfluoroalkyl substances in the water source from a typical agricultural area in North China - Wang, Xiaowei; Zhang, Hongwei; He, Xiaosong; Liu, Jianfei; Yao, Zhiliang; Zhao, Hongbin; Yu, Dayang; Liu, Baosen; Liu, Tianfu; Zhao, Weilong (Frontiers in Environmental Science, 2023)
There is limited information on per-/polyfluoroalkyl substances (PFASs) contaminations in the water source affected by agricultural activities. The contamination of PFASs were investigated in the sources of agricultural groundwater and nearby surface water from an important vegetable production base supply for Beijing and Tianjin, located in North China. ⅀13PFASs concentrations were found to be ranged from 0.321 to 8.285 ng/L with an average concentration of 2.022 ng/L in the groundwater, and 19.673 ng/L in the surface water. With the increase of the carbon chain length, the mean concentrations of PFASs in groundwater generally showed a decreasing trend. The dominated congeners of short-chain perfluorobutanesulfonate and perfluorooctanoate acid (PFOA) were detected in all groundwater samples, with mean concentrations of 0.944 and 0.654 ng/L. The difference was found that PFOA and perfluorooctanesulfonate (PFOS) were the dominated congeners in nearby surface water, with concentrations of 7.585 and 3.421 ng/L. Thus, the concentrations of PFOA and PFOS in the surface water were about 8.5 times higher than those in the groundwater, indicating that ⅀13PFASs concentrations might decrease with the water migration from overground to underground. In addition, significant correlations were observed between PFASs and DOC/TN related to agricultural activities, suggesting a certain relationship existed between PFASs congers distributions and organic carbon/nutrients in water. Health risk assessment indicated that the PFASs exposure caused insignificantly immediate harm to residents in the studied aera. This survey provided information on the sources, spatial distribution, and potential migration characteristics of PFASs in a typical agricultural aera of North China.